La posesión efectiva como requisito previo en la partición extrajudicial de bienes sucesorios - Martínez Felicito, Jorge Leonel (2025)
Effective possession as a requirement within the extrajudicial partition is an issue that has generated several discrepancies among legal professionals and those who have had an interest in it. For this reason, a legal, critical and doctrinal study has been carried out in order to identify whether the function of effective possession has been distorted when it is requested as a requirement instead of an inventory of inheritance assets for the extrajudicial partition. In this sense, the qualitative - quantitative paradigm has been used, which through the application of theoretical methods of knowledge such as inductive, document analysis, analytical - synthetic, it has been demonstrated that effective possession is sufficient for the heirs to be able to request the extrajudicial partition, in case there is someone who feels harmed for not having been taken into account in the partition when they had the right to do so, they will always have the actions that the law confers them as in the case of the right to petition for inheritance.